HARMONIZING THE CLASH OF SUFISM AND SHARIA IN AL GHAZALI’S THOUGH - Supriyadi Ahmad (Teosofia: Indonesian Journal of Islamic Mysticism, 2018)
Al-Ghazali is an expert and great Muslim scholar who speaks up for moderate Sunni sufism, a sufism which is based on the doctrine of the asceticism of the Qur'an, Prophetic traditions, and the tradition of his companions. He succeeded in purifying Sufism from various deviations, and harmonizing Sufism with sharia, and making it "halal" for Sunnis. According to al-Ghazali, several terms in Sufism should be returned to the original teachings of the Qur'an and Prophetic traditions. In his view, ma'rifah is knowing the secrets of God and His various rules about everything that exists. Heart becomes a means of understanding for a Sufi. So the highest and most noble pleasure is recognizing Allah Almighty, known as ma'rifah. A wise person (‘arif) does not see other than Allah, and everything he or she knows in this existance is only Him and His various creations. In the knowledge of Mukasyafah for example, al-Ghazali wanted to avoid the mistakes of other Sufis who transgressed, such as Abu Yazid al-Bustami and Abu Manshur al-Hallaj with their philosophical concepts which tended to be very complicated.